(untitled) (Sirte University Journal of Humanities, 2026)
This research evaluates the efficiency and adequacy of Libyan tax legislation, with particular focus on Income Tax Law No. (7) of 2010, in light of modern economic developments and the growing expansion of the digital economy. The study is based on the premise that the current tax law no longer aligns with the nature of emerging economic activities and lacks a sufficient legal framework to combat tax evasion—a phenomenon that has increased due to weak oversight and legislative and regulatory deficiencies. The research relies on an analytical review of legal texts, especially Electronic Transactions Law No. (6) of 2022, which fails to regulate taxation of digital activities. It further examines the economic and social impacts of tax evasion on public finance and calls for urgent legislative reforms to strike a balance between revenue collection and the protection of the investment environment. The study aims to enhance tax justice and improve the efficiency of the national financial system, thereby supporting sustainable economic development in Libya.